The Psychometric Properties of the Arabic Version of Nomophobia Scale among Omani Youth (Journal Of Educational and Psychological Researches, 2022)
The current research aimed to investigate the psychometric characteristics of the Arabic version of the Nomophobia scale for the Omani youth. The scale was administered to a random sample of students from public and private universities and colleges in Oman. The research sample consisted of 2507 students, of whom 868 males and 1639 females. The validity of the measure was first checked by presenting the scale to a group of experts in this field. Then the exploratory and confirmatory factor analysis was carried out. The exploratory factor analysis revealed the existence of three main factors: the fear of connectivity loss, the fear of communication loss with others, and the fear of network outages. These factors accounted for 65.6% of the total variance. The Corrected correlation coefficients for each item were calculated from the dimension to which they belonged and ranged from 0.59 to 0.78. The correlative validity of the scale was tested with the social networking addiction scale, and the correlation coefficient between the two measures was 0.63. For reliability of the scale, it was verified by using Cronbach alpha coefficient of the scale as a whole and its three dimensions showed as follows 0.83, 0.87, 0.91 and 0.94, respectively. Moreover, the Guttman split-half coefficient was calculated, which reached 0.87. These results confirm that the scale has high psychometric properties.